2014
DOI: 10.1089/ars.2012.5014
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Reactive Oxygen Species: Friends or Foes of Cancer Cells?

Abstract: More studies are needed to better understand the role of iron and ROS in carcinogenesis not only as cancer promoters, but also as cytotoxic agents to cancer cells and cancer stem cells (CSCs). Moreover, the structure-activity effects of iron chelators and other compounds that increase ROS and/or disrupt iron metabolism need to be further evaluated to assess the effectiveness and selectivity of these compounds against both cancer and CSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 49 publications
4
122
0
3
Order By: Relevance
“…8B). These data support the concept that moderate induction of ROS in cancer cells would contribute to cell proliferation rather than triggering cell death [42,45].…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 84%
See 1 more Smart Citation
“…8B). These data support the concept that moderate induction of ROS in cancer cells would contribute to cell proliferation rather than triggering cell death [42,45].…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 84%
“…S7). The tumorigenic effect of iron has been attributed to several factors, such as overproduction of ROS and free radicals through irondependent Fenton reaction, induction of oxidative responsive transcriptional factors and pro-inflammatory cytokines and iron-mediated hypoxia signaling [39][40][41][42]. Consistent with previous studies [43,44], we demonstrated that iron treatment (FAC 32 μM, similar to the mean iron concentration in our breast cancer patients) could induce about 1.9-fold increase of intracellular ROS level in MBA-MB-231 cells compared to the control (Fig.…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthmentioning
confidence: 99%
“…Hepcidin expression is fundamentally governed by the BMP family members (Andriopoulos et al, 2009) and the IL-6 family cytokines (Banzet et al, 2012) through erythropoietic demand, iron burden and inflammatory stimuli (Ganz, 2010). Hepcidin deficiency is associated with increased serum iron and leads to a few iron-related disorders, such as nervous system diseases (Jeong and David, 2003), hepatocirrhosis (Fei et al, 2006) and even cancers (Bystrom et al, 2012;Nemeth and Ganz, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1), resulting in enforced iron supply to other tissues including tumors. Excessive iron availability will enhance the rate of iron-dependent biological processes necessary for cell growth, and elevate the risk of genetic mutation via free radical production (Bystrom et al, 2014;Torti and Torti, 2011). It has been suggested that excessive iron can greatly increase the incidence of various cancers and neurological diseases (Ganz and Nemeth, 2011;Zhang et al, 2014).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…It has been suggested that excessive iron can greatly increase the incidence of various cancers and neurological diseases (Ganz and Nemeth, 2011;Zhang et al, 2014). Additionally, numerous studies have suggested the notable contribution of excess iron to tumor development (Bystrom et al, 2014;Richardson et al, 2009;Torti and Torti, 2011).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%